2015
DOI: 10.1016/j.habitatint.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Citizen satisfaction with public goods and government services in the global urban south: A case study of Cali, Colombia

Abstract: In this paper we present data from a recent survey of residents' satisfaction levels with a range of urban public goods and government performance in Cali, Colombia. The more affluent report higher levels of satisfaction, especially with regard to security, public space, utilities and government performance, compared to the poor. The low scoring on satisfaction with civic norms and government performance, especially amongst the poor, undermines the notion of an aspirations paradox, suggests a lack of social ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…This means that the higher the satisfaction with urban environments, the higher the livability. Previous studies have also shown the same relationship between these variables (Badland et al 2014;Buys and Miller 2012;De Vos and Witlox 2017;Ibem and Aduwo 2013;Marans and Stimson 2011;Martínez et al 2015;Tao et al 2014). More specifically, the accessibility was found to have the greatest impact on the sub-components of urban environments.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This means that the higher the satisfaction with urban environments, the higher the livability. Previous studies have also shown the same relationship between these variables (Badland et al 2014;Buys and Miller 2012;De Vos and Witlox 2017;Ibem and Aduwo 2013;Marans and Stimson 2011;Martínez et al 2015;Tao et al 2014). More specifically, the accessibility was found to have the greatest impact on the sub-components of urban environments.…”
Section: Discussionsupporting
confidence: 65%
“…It is promoted as one of the important factors that make up urban environments. Many studies assert that satisfaction with urban environments is closely related to crime rates or accident rates (De Vos and Witlox 2017;Ibem and Aduwo 2013;Marans and Stimson 2011;Martínez et al 2015). For example, Buys and Miller (2012) found that safety was an important factor in residential satisfaction in cities with high population density (e.g., in Brisbane, Australia).…”
Section: Safetymentioning
confidence: 99%
“…Finally, safety satisfaction refers to satisfaction with safety in a residential area from disasters or accidents, and comprises a rapid response to accidents or disasters and well-established emergency medical systems. Previous studies have found that the safer a community is, the better the QoL is [39][40][41]. Based on these discussions, the following hypothesis is proposed.…”
Section: Relationship Between Physical Environment Satisfaction and Qolmentioning
confidence: 99%
“…Para complementar esta idea, Easterlin (2001) observó cómo los altos ingresos económicos de personas con vidas muy agitadas son proporcionales al aumento de sus expectativas, lo que los hace infelices o intranquilos al no poder satisfacer sus necesidades. Otro aspecto importante es la edad y las necesidades derivadas de esto, específicamente en las personas mayores, ya que la satisfacción de las necesidades y el bienestar están estrechamente relacionados con la salud, las habilidades motoras y las dificultades relacionadas con el acceso a los espacios (Martínez, Short y Ortíz, 2015). c onFoRmAción de GRupos bAjo lA noRmA sociAl De acuerdo con Espinosa (2000), los asentamientos poblacionales tienden a organizarse en torno a hábitos comunes entre individuos, además de metas, ideales y actividades compartidas que generan afinidad.…”
Section: Bienestar En Espacios De Contemplaciónunclassified